2011
DOI: 10.1016/j.ajpath.2011.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fibroblast Growth Factor-Binding Protein–1 Expression on Angiogenesis and Wound Healing

Abstract: Fibroblast growth factors (FGFs) participate in embryonic development, in maintenance of tissue homeostasis in the adult, and in various diseases. FGF-binding proteins (FGFBP) are secreted proteins that chaperone FGFs stored in the extracellular matrix to their receptor, and can thus modulate FGF signaling. FGFBP1 (alias BP1, FGF-BP1, or HBp17) expression is required for embryonic survival, can modulate FGF-dependent vascular permeability in embryos, and is an angiogenic switch in human cancers. To determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 65 publications
3
60
0
Order By: Relevance
“…New vessel formation (angiogenesis) is an essential physiological process in embryonic development, normal growth, and tissue repair (Tassi et al, 2011). Angiogenesis is tightly regulated at the molecular level; however, this process is dysregulated in several pathological conditions such as cancer (Rapisarda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…New vessel formation (angiogenesis) is an essential physiological process in embryonic development, normal growth, and tissue repair (Tassi et al, 2011). Angiogenesis is tightly regulated at the molecular level; however, this process is dysregulated in several pathological conditions such as cancer (Rapisarda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exogenously added FGF-BP1 enhances keratinocyte migration. 16 Together with the finding that expression levels of the fgfbp1 transgene were particularly high in keratinocytes of the epidermis and the hair follicles, 6 this finding indicates that re-epithelialization may also be accelerated in the FGF-BP1 transgenic mice. Indeed, the accelerated wound closure that was observed in these animals supports this hypothesis, although it remains to be determined whether this resulted from enhanced contraction and/or from enhanced re-epithelialization.…”
Section: Fgf-bp1 Enhances Angiogenesis Fibroblast Migration and Woumentioning
confidence: 82%
“…Thus, Tassi et al 6 also demonstrated that FGF-BP1 enhances angiogenesis in the mouse ischemic hindlimb muscles. Furthermore, the expression of FGF-BP is increased in regenerating renal tubular epithelial cells, indicating a role in kidney repair.…”
Section: Fgf-bp1 Enhances Angiogenesis Fibroblast Migration and Woumentioning
confidence: 91%
See 2 more Smart Citations